Perancangan Mesin Pengupas Kulit Ari Kopi dengan Model Preskiptif Pahl & Beitz - Prasetyo, Prasetyo; Kurnia, Muhammad Adly; Widiantoro, Heri (Mechanical Engineering Department - Semarang State Polytechnic, 2022)
The process of stripping the epidermis of coffee beans is an important process before the coffee bean roasting process is carried out. One of the post-harvest machines for coffee beans is a huller. As the coffee bean huller developed, there were many variations in the process. In this study, a coffee huller was designed using the Pahl & Beitz prescriptive model. The design stage of the Pahl & Beitz model includes initial planning, conceptual design, embodiment design, and detail design. The results of the design include 3D models using the SolidWorks application. The calculation results produce machine specifications in the form of motor design power of 0,5 kW; transmission using V-belt number A53 (L = 1346 mm), the number of belts are 2, pulley diameter 95mm, pulley width 35mm, adjustment distance (504 —564) mm; shaft diameter 25mm; as well as the width and height of the stake 7mm. Keywords: Coffee, Design, Machine Design, Post-Harvest